Evolution of Adult Cervical Deformity Surgery Clinical and Radiographic Outcomes Based on a Multicenter Prospective Study: Are Behaviors and Outcomes Changing With Experience?. Issue 22 (15th November 2022) - Passias, Peter G.; Krol, Oscar; Moattari, Kevin; Williamson, Tyler K.; Lafage, Virginie; Lafage, Renaud; Kim, Han Jo; Daniels, Alan; Diebo, Bassel; Protopsaltis, Themistocles; Mundis, Gregory; Kebaish, Khaled; et al.
Abstract : Study Design: Retrospective cohort study. Objective: Assess changes in outcomes and surgical approaches for adult cervical deformity surgery over time. Summary of Background Data: As the population ages and the prevalence of cervical deformity increases, corrective surgery has been increasingly seen as a viable treatment. Dramatic surgical advancements and expansion of knowledge on this procedure have transpired over the years, but the impact on cervical deformity surgery is unknown. Materials and Methods: Adult cervical deformity patients (18 yrs and above) with complete baseline and up to the two-year health-related quality of life and radiographic data were included. Descriptive analysis included demographics, radiographic, and surgical details. Patients were grouped into early (2013–2014) and late (2015–2017) by date of surgery. Univariate and multivariable regression analyses were used to assess differences in surgical, radiographic, and clinical outcomes over time. Results: A total of 119 cervical deformity patients met the inclusion criteria. Early group consisted of 72 patients, and late group consisted of 47. The late group had a higher Charlson Comorbidity Index (1.3 vs. 0.72), more cerebrovascular disease (6% vs. 0%, both P <0.05), and no difference in age, frailty, deformity, or cervical rigidity. Controlling for baseline deformity and age, late group underwent fewer three-column osteotomies [odds ratio (OR)=0.18, 95% confidence interval (CI): 0.06–0.76, P =0.014]. At the last follow-up, late group had less patients with: a moderate/high Ames horizontal modifier (71.7% vs. 88.2%), and overcorrection in pelvic tilt (4.3% vs. 18.1%, both P <0.05). Controlling for baseline deformity, age, levels fused, and three-column osteotomies, late group experienced fewer adverse events (OR=0.15, 95% CI: 0.28–0.8, P =0.03), and neurological complications (OR=0.1, 95% CI: 0.012–0.87, P =0.03). Conclusion: Despite a population with greater comorbidity and associated risk, outcomes remained consistent between early and later time periods, indicating general improvements in care. The later cohort demonstrated fewer three-column osteotomies, less suboptimal realignments, and concomitant reductions in adverse events and neurological complications. This may suggest a greater facility with less invasive techniques.